PLAY! Fun, facts, and the construction of engagement in the LEGOLAND theme parks website - Stefania Consonni (Scripta Manent)
As digital communication has been challenging traditional monomodality, and as tourist offer has been increasing over the last decades, the language of tourist promotion in the Web has progressively been evolving into a multilayered and multiliteracy model, bridging verbal and visual language in a new semiotic integration code, which includes impactful, highly persuasive mass and multimedia products, such as tourist promotion websites. As a consequence, LSP students are nowadays confronted with increasingly complex semiotic artefacts. The pedagogical significance of multimodal analysis to the work/practice of learners/teachers of LSP, tourism discourse and Web communication thus comes into focus. This paper addresses the mixed-media strategies constructing the LEGOLAND theme park website as a recreational destination on the Web as a significant case study for multiliteracy communication. Drawing from the metafunctions (i.e., ideational, interactional, textual) of Systemic Functional Grammar, from socio-semiotic multiliteracy analysis, and from multimodal genre analysis of tourism and communication discourse, the paper will investigate the textual/visual strategies through which audience engagement is created in the LEGOLAND website. In particular, at the ideational level, the paper will analyse the key role played by the representation of informative meanings in the website’s promotional purposes; at the interactional level, the metadiscursive strategies maximizing audience involvement will be investigated; and at the textual level, the thematic structure and Information Unit patterning of the LEGOLAND website will be explored, in order to examine the specialzed meaning-making resources which should be made accessible to tourism and communication discourse learners.